Push or pull? Unpacking the social compensation hypothesis of Internet use in an educational context. (June 2017) - Grieve, Rachel; Kemp, Nenagh; Norris, Kimberley; Padgett, Christine R.
Abstract: Individual differences such as social anxiety and extraversion have been shown to influence education outcomes. However, there has been limited investigation of the relationship between individual differences and attitudes towards online and offline learning. This study aimed to investigate for the first time how social anxiety and extraversion influence student attitudes to online and offline learning, specifically in relation to tertiary level practical activities. Based on the social compensation hypothesis, it was predicted that students with higher levels of extraversion and lower levels of social anxiety would report more favourable attitudes to face-to-face learning activities. It was further predicted that less extraverted and more socially anxious students would have more favourable attitudes to online learning activities. Undergraduate students ( N = 322, 67% female) completed the HEXACO-60 personality inventory, the Mini Social Phobia Inventory, and measures of attitudes towards online and offline activities. Two hierarchical multiple regressions were conducted. The first revealed that neither extraversion nor social anxiety contributed significantly to preference for online practical activities. The second regression revealed that greater emotionality, greater extraversion, greater conscientiousness, and lower levels of social anxiety were associated with more favourable attitudes towards face-to-face practical activities. In contrast to predictions, extraversion and social anxiety did not significantly contribute to attitudes to online learning activities. However, in line with predictions, greater extraversion and lower levels of social anxiety were associated with more favourable attitudes towards face-to-face practical activities. These findings indicate that online learning activities have limited compensatory effects for students who experience social discomfort, and that the social compensation hypothesis may apply within an educational framework, but in unexpected ways. Highlights: Applies the social compensation hypothesis of Internet use as a theoretical paradigm. Examines role of social anxiety (SA) and extraversion in online and offline learning. Extraversion and SA not associated with attitudes to online activities. Extraversion and low SA positively predict face-to-face activity attitudes. Online learning has limited compensatory effects for socially anxious students.